Iron‐Catalyzed Dehydropolymerization: A Convenient Route to Poly(phosphinoboranes) with Molecular‐Weight Control1. Issue 16 (25th February 2015) - Schäfer, André; Jurca, Titel; Turner, Joshua; Vance, James R.; Lee, Kajin; Du, Van An; Haddow, Mairi F.; Whittell, George R.; Manners, Ian
Abstract The catalyst loading is the key to control the molecular weight of the polymer in the iron‐catalyzed dehydropolymerization of phosphine–borane adducts. Studies showed that the reaction proceeds through a chain‐growth coordination–insertion mechanism.